Sensitization of Xanthophylls-Chlorophyllin Mixtures on Titania Solar Cells - Indriana Kartini; L. Dwitasari; T. D. Wahyuningsih; Chotimah Chotimah; L. Wang (International Journal of Science and Engineering, 2015)
Co-sensitization of natural dyes on TiO2 for dye-sensitized solar cell (DSSC) was proposed between chlorophyllin (C) and xanthophylls (X at various volume ratios of C/X. Chlorophyllin is chlorophyll derivative providing -COOH groups essential for binding to TiO2. The chlorophyll was extracted from dried spinach (amaranthus viridis) leaves in a mixture of methanol-acetone (70%:30%). Chlorophyll extract dye was obtained after partition of the crude extracts in diethyl ether solution. Then, it was hydrolyzed under alkaline condition to get chlorophyllin. Xanthophyll was extracted from fresh petal of chrysanthemum (chrysanthemum indicum) flowers. Blending of chlorophyllin and xanthophyll was carried out at various volume ratios of C to X (1:0, 5:1, 1:1, 1:5, 0:1). Titania solar cells were constructed in sandwich system of conducting glass-titania/dyes as the photoanode and conducting glass-platinum as the photocathode. Electrolyte solution containing I-/I3- was inserted between the electrodes by capillary action. All dye extracts and blending solutions were analyzed by UV-Vis spectrophotometer. It is shown that the absorption spectra of blending dyes are complimentary in the visible region resulted in a panchromatic response of the dyes. From the cyclic voltammogram of the dyes and blended-dyes, it is found that the energy level of xanthophyll is the lowest. The I-V test at 100 mw/cm2 irradiation confirmed that the energy conversion efficiency (h) of the blended dyes of xanthophyll and chlorophyllin-sensitized solar cell resulted in significant improvement than those of the single dye. Beneficially, the mixed dyes can be adsorbed from solution blend using single dipping step.